Semi-synthesis of novel 1,4-disubstituted-1,2,3-triazole derivatives of penicillin G and their antibacterial activity - Rasoolijokari, Kaveh; Salehi, Peyman; Aliahmadi, Atousa; Heidari, Bahareh; Bararjanian, Morteza (Phytochemistry letters, 2023)
A series of 12 novel 1,2,3-triazole penicillin G derivatives were subject to synthesis starting from propargylation of penicillin G followed by copper(I) catalyzed azide alkyne cycloaddition (CuAAC) click reaction. Also, one-pot Strecker reaction was applied aiming for the preparation of 5 novel α-amino nitrile triazole tethered penicillin G derivatives. The derivatives’ chemical structures were confirmed by means of 1H NMR, 13C NMR, FT-IR, and HR-MS. The synthesized compounds (5a-5 l and 10a-10e) were evaluated in vitro as antimicrobial agents against Staphylococcus aureus plus Enterococcus faecalis as Gram-positive and Escherichia coli as Gram-negative bacteria, and the ultimate results were compared with penicillin G. Compounds 5a and 5b revealed the uppermost potency in inhibiting bacterial growth with the minimum inhibitory concentration (MIC) value of 0.049 µg/ml against S. aureus. Amongst α-amino nitrile derivatives, 10d and 10e exhibited greater potency in inhibiting bacterial growth (MIC=0.19 µg/ml) against S. aureus. Moreover, an investigation of minimum bactericidal concentration (MBC) of 5a-5 l and 10a-10e derivatives put on display the fact that 5b and 5 h were potent to kill the assessed S. aureus cells in concentration just two fold above that of penicillin G’s. [Display omitted] •A series of novel 1,2,3-triazole penicillin G derivatives were synthesized.•Antimicrobial agents have been investigated against Gram-positive bacteria.•The products depicted promising effects compared to that of penicillin G’s.